Economic metaphors in political discourse: a cognitive linguistic study of Indonesian presidential debates - Radna Tulus Wibisono (Indonesian Journal of Language and Economic Discourse, 2026)
Background: Economic debates in Indonesia’s presidential elections are not merely policy exchanges but discursive contests where metaphors shape public understanding of governance and legitimacy. Objective: The purpose of this study is to examine how economic metaphors frame political discourse in the 2019 and 2024 Indonesian presidential debates. Method: Using a mixed-methods design, the research integrates Cognitive Metaphor Theory, Critical Discourse Analysis, and Corpus Linguistics, drawing data from official KPU transcripts, debate videos, and media reports. Results: The results show, first, that dominant conceptual metaphors include STATE AS FIRM (negara sebagai perusahaan), BUDGET AS FLUID (anggaran sebagai cairan), and ECONOMY AS ENGINE (ekonomi sebagai mesin), which simplify abstract economic policies. Second, ideological positioning is evident, with opposition candidates emphasizing crisis metaphors, incumbents employing growth and stability frames, and both sides using redistribution metaphors to claim moral authority. Third, corpus analysis highlights frequent clusters such as pertumbuhan ekonomi, investasi asing, anggaran bocor, and subsidi tepat sasaran, which anchor economic debates around growth, efficiency, and fairness. Implication: The implications suggest that metaphors function as powerful framing devices that not only clarify but also constrain democratic discourse, shaping voter cognition and perceptions of legitimacy. Novelty: This study shows how economic metaphors function as cognitive and ideological framing devices that structure political contestation and shape public perceptions of governance and legitimacy in electoral debates.